The Implementation of Differentiated Instruction in Islamic Religious Education to Enhance Students’ Learning Motivation - Nana Supriatna; Abdul Holik (Journal of Science and Education (JSE), 2025)
This study aims to examine the implementation of differentiated instruction in Islamic Religious Education (IRE) as a strategy to enhance elementary school students’ learning motivation. Employing a classroom action research approach with a mixed-methods design, the research was conducted at SDN Leuwiliang and SDN Pelita, both of which have adopted the Merdeka Curriculum. Data were collected through the Motivated Strategies for Learning Questionnaire (MSLQ), classroom observations, in-depth interviews, and documentation of the instructional process. The findings indicate that learning style-based differentiation strategies such as the use of podcasts for auditory learners and worship practice simulations for kinesthetic learners effectively increased student engagement. Content differentiation through the integration of local culture and tiered assignments also significantly reduced the rate of learning incompleteness. Quantitative analysis revealed a significant improvement in intrinsic goal orientation scores (from μ = 2.1 to μ = 3.4) and self-efficacy (from μ = 2.3 to μ = 3.6), with p < 0.018. The successful implementation was further supported by educational technology, teacher collaboration, and principal-led budgeting policies. These findings affirm that differentiated instruction in IRE not only enhances learning motivation but also fosters a more inclusive and contextualized learning experience. The study recommends the development of technical guidelines, reflective training for IRE teachers, and school policies that are responsive to diverse learning needs.